1984
DOI: 10.1159/000299127
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Study in 50 Couples with Recurrent Abortions

Abstract: The presence of chromosome abnormalities in couples with repeated spontaneous abortion is known even if the phenomenon is far from a complete assessment. A cytogenetic investigation in 50 couples with a history of two or more spontaneous abortions is referred to in this study. A peripheral blood lymphocyte culture was harvested for each subject and the slides were stained by G- and C-banding. Of the 100 individuals examined, 4 were carriers of balanced translocations, 3 of which were of the Robertsonian type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…CAs are responsible for at least half of spontaneous abortions or miscarriages and are an important cause of congenital malformations [2][3][4]. Many other studies reported different frequencies varying between 0 and 17% [7][8][9][10][11][12]. In the present study, an incidence of 4.4% for chromosomal abnormality among patients with a bad obstetric history was found out.…”
Section: Resultssupporting
confidence: 49%
“…CAs are responsible for at least half of spontaneous abortions or miscarriages and are an important cause of congenital malformations [2][3][4]. Many other studies reported different frequencies varying between 0 and 17% [7][8][9][10][11][12]. In the present study, an incidence of 4.4% for chromosomal abnormality among patients with a bad obstetric history was found out.…”
Section: Resultssupporting
confidence: 49%
“…[1] Patients carrying balanced reciprocal translocation are subject to meiosis nondisjunction risk. Indeed, the mispairing of translocated chromosomes during the first meiotic division can give rise to different forms of segregation, which can result in aneuploidy of the translocated chromosomes.…”
Section: Introductionmentioning
confidence: 99%